SMART-ly Managing Type 1 Diabetes - Modifying Glucose Metabolism With an Online Mind-Body Intervention: A Feasibility and Pilot Study - Stahl, James E.; Ammana, Hima R.; Kwak, Leigh; Comi, Richard J. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Objective: Managing type 1 diabetes is stressful. Stress physiology influences glucose metabolism. Continuous glucose monitors allow us to track glucose variability in the real-world environment. Managing stress and cultivating resiliency should improve diabetes management and reduce glucose variability. Research design and Methods: The study was designed as a randomized prospective cohort pre-post study with wait time control. Participants were adult type 1 diabetes patients who used a continuous glucose monitor and recruited from an academic endocrinology practice. The intervention was the Stress Management and Resiliency Training (SMART) program conducted over 8 sessions over web-based video conference software. The primary main outcome measures were:were Glucose variability, the Diabetes Self-Management questionnaire (DSMQ), Short-Form Six-Dimension (SF-6D), and the Connor-Davidson Resiliency (CD-RSIC) instrument. Results: Subjects sawThere was statisticalstatistically significant improvement in their participants DSMQ and CD RISC scores though their the SF- 6D did not change. Subjects Participants under age 50 years-old sshowed aaw statistically significant reduction in their average glucose (p = .03) and Glucose Management Index (GMI) (p = .02). They also sawParticipants also had reducedtion in the percentage of time high and increased time in range though this did not reach statistical significance. The subjects participants found doing the intervention online acceptable if not always ideal. Conclusions: An 8-session stress management and resiliency training program significantly reduced diabetes related stress and improved resiliency and significantly reduced average blood glucose and GMI in those under 50 years-old.